2012
DOI: 10.1093/cid/cis889
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Consultation Cannot Replace Bedside Infectious Disease Consultation in the Management of Staphylococcus aureus Bacteremia

Abstract: Telephone IDS consultation is inferior to bedside IDS consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
135
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(150 citation statements)
references
References 26 publications
6
135
2
3
Order By: Relevance
“…Second, while this was a multihospital study, the main intervention was performed by only four or five infectious diseases specialists, and outcomes at other community hospitals may differ. In contrast to our setting, not all community hospitals have IDC available or they may have access only to telephone consultation, which was shown previously to be suboptimal (20). While most of the data, including the primary outcomes, were extracted objectively from electronic health records, other information (such as Pitt bacteremia scores and findings regarding complicated versus uncomplicated bacteremia) had to be collected manually.…”
Section: Discussionmentioning
confidence: 99%
“…Second, while this was a multihospital study, the main intervention was performed by only four or five infectious diseases specialists, and outcomes at other community hospitals may differ. In contrast to our setting, not all community hospitals have IDC available or they may have access only to telephone consultation, which was shown previously to be suboptimal (20). While most of the data, including the primary outcomes, were extracted objectively from electronic health records, other information (such as Pitt bacteremia scores and findings regarding complicated versus uncomplicated bacteremia) had to be collected manually.…”
Section: Discussionmentioning
confidence: 99%
“…Consultation with an infectious disease specialist is important for improving the proper selection of antimicrobial agents, altering the therapy duration, and improving the outcome in cases involving infectious diseases [11,12]. In particular, it was noted that bedside consultation, defined as an infectious disease specialist writing comments regarding the patient's status (based on the results of a physical examination) into in their patient record, is superior to telephone-based consultation [13]. Prior to 2013, most of the decisions regarding the management of antimicrobial treatment in our pediatric ward were made by non-specialists.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of SAB is impaired by high age [25], hemodynamic instability [24] and complications like endocarditis or pneumonia [24] whereas deep infection focus identification [4,5] and infectious disease specialist consultation have improved outcome [2,3,5]. Despite advances in SAB management, mortality remains high, ranging from 20%-32% in recent studies [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Median antimicrobial treatment durations in previous reports have been at least 2 week [8,9]. Recent studies have demonstrated that a vast amount of deep infection foci are present already within 3 days [4] and up to 80% of SAB patients present with a deep infection focus [4,5,13]. Furthermore, meticulous deep infection focus localization and infectious disease specialist consultations are known to improved SAB prognosis [2,4,5,13].…”
Section: Introductionmentioning
confidence: 99%